2020
DOI: 10.5430/rwe.v11n5p100
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Social Media Marketing Adoption Towards Business Performance: An Approach of Structural Equation Modelling Partial Least Square (SEM-PLS)

Abstract: Business environment in Malaysia has become more competitive due to the advancement of technology and globalisation including the small and medium enterprises (SMEs). SMEs have so long devised various marketing strategies in order to penetrate the online advertisement clutter alongside improving their performance. Past studies have shown that using ICT such as social media help to improve SMEs’ performance. The owner-managers themselves determine the adoption of social media in their marketing due to the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…In Western Australia, Gengatharen et al (2005) found that governmental support encouraged SMME marketing innovation, such as in their degree of e-marketing adoption. These findings have also been confirmed in Malaysian SMMEs (Samat et al, 2020). Thus, the following hypothesis is proposed:…”
Section: Governmental Supportsupporting
confidence: 53%
See 1 more Smart Citation
“…In Western Australia, Gengatharen et al (2005) found that governmental support encouraged SMME marketing innovation, such as in their degree of e-marketing adoption. These findings have also been confirmed in Malaysian SMMEs (Samat et al, 2020). Thus, the following hypothesis is proposed:…”
Section: Governmental Supportsupporting
confidence: 53%
“…Compared with a covariance-based SEM, PLS-SEM has more relaxed conditions for its use and is more suitable for testing mediation; thus, it is known as the “silver bullet” of research (Hair et al , 2011). Relevant to our study, PLS-SEM has recently been used in marketing innovation studies (Costa and Didonet, 2020; Samat et al , 2020) and knowledge management research (Bjorvatn and Wald, 2020).…”
Section: Methodsmentioning
confidence: 97%
“…Some of the studies that have been discussed by previous researchers explain that there are several important things in achieving good company performance. Research conducted by ; Ahmad et al (2018); Effendi et al (2020) and Samat et al (2020) concluded that there is a relationship between the technological context, organization, and environment to company performance with the help of mediation of marketing adoption through social media. Other studies discussed by Chatterjee & Kumar Kar (2020); Gavino et al (2019); Patma et al (2021); Pranoto & Lumbantobing (2021) found that there are other factors that affect the company's performance.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the case with the opinion that Ahmad et al (2018) and Alkateeb & Abdalla (2021) in their research found that there is no positive relationship between variables caused by companies that consider that technology is no longer a special thing and has become a common thing for companies to use. It is further concluded by Samat et al (2020) that the management of the company has a must to accept and realize the positive side of technology in the aim of utilizing social media as a useful marketing tool.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation